Exploring the Relationship Between Language of Instruction and Academic Achievement Among Primary School Students: Evidence from UAE (Global Journal of Human-Social Science, 2024)
We explore the impact of the language of instruction on academic performance of Emirati students who are expected to learn mathematics and science in and through a second language. Using TIMSS 2019 standardized tests and employing propensity score technique we explain the differences in achievement in mathematics and science between two groups of young Emirati children living in an Arabic dialect-dominated environment who get instruction in English and who receive instruction in classical Arabic. Our findings indicate that students who receive instruction in English have lower odds of attaining higher achievement scores.
Keywords: TIMSS; native language; second language; students’ performance; propensity score technique